Evaluation of the Panbio dengue virus nonstructural 1 antigen detection and immunoglobulin M antibody enzyme-linked immunosorbent assays for the diagnosis of acute dengue infections in Laos. - Blacksell, S; Mammen, M; Thongpaseuth, S; Gibbons, R; Jarman, R; Jenjaroen, K; Nisalak, A; Phetsouvanh, R; Newton, P; Day, N (2008)
We evaluated 2 commercial enzyme-linked immunosorbent assays (ELISAs) for the diagnosis of dengue infection; one a serologic test for immunoglobulin M (IgM) antibodies, the other based on detection of dengue virus nonstructural 1 (NS1) antigen. Using gold standard reference serology on paired sera, 41% (38/92 patients) were dengue confirmed, with 4 (11%) acute primary and 33 (87%) acute secondary infections (1 was of indeterminate status). Sensitivity of the NS1-ELISA was 63% (95% confidence interval [CI], 53-73) on admission samples but was much less sensitive (5%; 95% CI, 1-10) on convalescent samples. The IgM capture ELISA had a lower but statistically equivalent sensitivity compared with the NS1-ELISA for admission samples (45%; 95% CI, 35-55) but was more sensitive on convalescent samples (58%; 95% CI, 48-68). The results of the NS1 and IgM capture ELISAs were combined using a logical OR operator, increasing the sensitivity for admission samples (79%; 95% CI, 71-87), convalescent samples (63%; 95% CI, 53-73), and all samples (71%; 95% CI, 65-78).